Innovation in Citizenship Learning At Rk Makmur Primary School: Utilizing Technology to Increase Social and Political Awareness - Saragih, Rosvilani; Rezky, Sri; Fahira, Rachyana; Yunita, Sri; Ndona, Jacobus (Budapest International Research and Critics University, 2024)
Citizenship learning at the RK Makmur Elementary School level is an important part in forming students' social and political awareness to become active and responsible citizens. In the current digital era, learning innovation by utilizing technology is becoming increasingly relevant and important for improving the quality of civic learning. This research aims to explore the implementation of civic learning innovations that utilize technology at the RK Makmur Elementary School level and its impact on increasing students' social and political awareness. Through literature analysis and related research results, we develop effective citizenship learning strategies by utilizing technology, such as interactive e-learning platforms, social media, online games, and educational applications. We also discuss important components in implementing civic learning innovations with technology, including selecting appropriate technology, goal-oriented learning design, using engaging media, effective classroom management, technology-based evaluation, and project-based collaborative learning. The research results show that civic learning innovations with technology have great potential to increase student involvement, their understanding of socio-political issues, and their awareness of their rights and obligations as citizens. However, challenges such as equitable access to technology and required teacher training also need to be addressed to maximize the potential of civic learning with technology. This research provides an important contribution to the understanding of the potential of technology in improving citizenship education at the RK Makmur elementary school level and offers an in-depth view of how learning innovations with technology can form citizens who are active, critical and participate in democratic life.